Molecular characterisation of Pea seed borne mosaic poytvirus associated with apical rosette in field pea (Pisum sativum L.) in India. (14th December 2021) - Kamaal, Naimuddin; Akram, Mohammad
Abstract: Symptoms of apical rosette were seen in field pea grown as winter season crop in India. Symptomatic leaves were processed for the identification of associated virus. The primers pair (PSbMV-F/PSbMV-R) targeting part of NIb gene of Pea seed borne mosaic potyvirus (PSbMV) was used in RT-PCR. The targeted fragment was successfully amplified cloned and sequenced. Sequencing of amplicons revealed it to be 795 bp long and identical to each other and hence only one was deposited to the NCBI database. Blast results of sequence showed it to be a portion of NIb region of the PSbMV and had 100–88.5% nt similarity with known isolates of the PSbMV. Phylogenetic analysis revealed that all the PSbMV isolates used group together. However, the PSbMV-IN:Knp isolate sub-clustered with the known PSbMV isolates of pathotype 1. This is the first report of the characterisation of an Indian isolate of PSbMV based on genomic sequence.